2016
DOI: 10.1101/090860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New genes and functional innovation in mammals

Abstract: The birth of genes that encode new protein sequences is a major source of evolutionary innovation.However, we still understand relatively little about how these genes come into being and which functions they are selected for. To address these questions we have obtained a large collection of mammalian-specific 5 gene families that lack homologues in other eukaryotic groups. We have combined gene annotations and de novo transcript assemblies from 30 different mamalian species, obtaining about 6,000 gene families… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 104 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…We next sought to identify which features in the mRNA could explain the discrepancy of mRNA and protein expression. High sequence conservation has been associated with high gene expression levels in mammals (Villanueva-Cañas et al, 2017). We therefore questioned whether this was also true for both mRNA and protein abundance in PMA-Ionomycin activated CD8 + T cells.…”
Section: Gene and Transcript Characteristics Influence Mrna And Protementioning
confidence: 96%
“…We next sought to identify which features in the mRNA could explain the discrepancy of mRNA and protein expression. High sequence conservation has been associated with high gene expression levels in mammals (Villanueva-Cañas et al, 2017). We therefore questioned whether this was also true for both mRNA and protein abundance in PMA-Ionomycin activated CD8 + T cells.…”
Section: Gene and Transcript Characteristics Influence Mrna And Protementioning
confidence: 96%
“…Such noncoding RNAs most often derive from mobile genetic elements and are the major contributors to regulatory ncRNAs, which include endogenous retroviruses, their defective derivatives, and other persistent genetic parasites (not forgetting their degraded parts). [35][36][37][38][39][40] Another highly interesting interaction motif of RNAs is the RNA fragments that self-ligate into selfreplicating ribozymes, which spontaneously form cooperative networks. It was found that the threemembered RNA networks showed highly cooperative growth dynamics.…”
Section: Rna Populations and Their Historical Backgroundmentioning
confidence: 99%
“…For example, lineage-specific genes have been interpreted as "de novo genes" that have evolved from previously noncoding sequence [10,11], and as duplicated genes that diverged radically in evolving a new function [12]. Though different in detail, these proposals share the key assumption that a lack of detectable homologs indicates some kind of biological novelty: lineage-specific genes either have no evolutionary homologs or no longer perform the same function as their homologs outside the lineage [13][14][15][16]. We refer to these interpretations collectively as the "novelty hypothesis" of lineage-specific genes.…”
Section: Introductionmentioning
confidence: 99%